Resolving Illegal Fishing in Rumpon Unjam: The Strategic Role of Panglima Laot in Aceh's Customary Law - Sholihin, Riadhus; Husna, Nurul; Irwansyah, Irwansyah; Maulana, Wahyu; Raihan, Ishma (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Illegal fishing is a crime that causes one party to suffer losses. Consequently, fishing activities in Indonesian waters must adhere to the regulations. The purpose of creating a legal regulation is to establish a provision and legal protection in order to maintain peace within an organisation in the event of a conflict. In this instance, the existence of panglima laot in carrying out the function of customary law is one of the role models for the order of community life in resolving the issue of unauthorized fishing on Rumpon Unjam or other people's platforms. This research seeks to determine how the mechanism for resolving illegal fishing in Rumpun Unjam is governed by customary law with the function of panglima laot, as well as the review of Islamic law on the mechanism for resolving illegal fishing in Rumpon Unjam under customary law with the function of panglima laot. This research uses field research as its methodology. Among the methods of data collection are observation and interviews. The findings of this study indicate that the mechanism for resolving illegal fishing crimes in Rumpon Unjam, which are resolved by customary law by the Sea commander, is appropriate because the customary law imposed on the perpetrator requires a deterrent effect so that he or she will not repeat the same act by receiving appropriate sanctions for the sake of justice for the victim. According to a review of Islamic law, the mechanism for resolving illegal fishing crimes in Rumpun Unjam people who are resolved by custom by the commander of the laot is in accordance with the punishment recommended by the Qur'an because it uses ta'zir law, which is a punishment decision from the regional ruler, and the punishment imposed is appropriate retribution for the actions committed. When viewed from the victim's perspective, the imposed punishment is consistent with Islamic law because it satisfies the victim's sense of justice.